Research Skills of Prospective Biology Teacher: An Analysis for Development Needs - Trisna Amelia (Pedagogi Hayati, 2023)
This study was conducted to determine the extent to which research skills have been mastered by prospective biology teacher in learning at universities and to determine the need for developing research skills. Research skills are defined as skills using information literacy and basic biology laboratory skills related to research. An analysis of curriculum documents and examples of RPS from the biology education study program at one of the universities in the Kepulauan Riau Province was carried out to explore lecture designs that prepare students' research skills. A total of 25 alumni (graduates) of the study program were involved in a perception survey of how important research skills are for them in the workplaces. 27 final year students were also involved in providing self-assessments about their ability to master information literacy and basic biology laboratory skills. Data was analyzed qualitatively and quantitatively. Data analysis resulted that the researcher profile is one of the targets for graduates of biology education study programs but has not been supported by course designs. Research skills are needed by alumni in the workplaces and are very relevant to support their careers. Information literacy and basic biology lab skills have not been fully mastered by final year students. There is an urgency to equip students with more adequate skills so that students are better able to carry out research, including completing their studies.